2014
DOI: 10.1371/journal.pone.0110152
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Communities in Semen from Men of Infertile Couples: Metagenomic Sequencing Reveals Relationships of Seminal Microbiota to Semen Quality

Abstract: Some previous studies have identified bacteria in semen as being a potential factor in male infertility. However, only few types of bacteria were taken into consideration while using PCR-based or culturing methods. Here we present an analysis approach using next-generation sequencing technology and bioinformatics analysis to investigate the associations between bacterial communities and semen quality. Ninety-six semen samples collected were examined for bacterial communities, measuring seven clinical criteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
267
0
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(316 citation statements)
references
References 68 publications
19
267
0
13
Order By: Relevance
“…In both studies, high numbers of anaerobic bacteria were found. Some studies have recently used the NGS method to detect bacteria in semen . Weng et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both studies, high numbers of anaerobic bacteria were found. Some studies have recently used the NGS method to detect bacteria in semen . Weng et al .…”
Section: Discussionmentioning
confidence: 99%
“…Weng et al . investigated the male partners of infertile couples, and found that the proportions of Lactobacillus and Gardnerella were higher in the normal samples, whereas that of Prevotella in the low‐quality samples . Hou et al .…”
Section: Discussionmentioning
confidence: 99%
“…It is logical, given the abundance of amino acids and other nutritional substrates in basic seminal fluid, that it would promote bacterial growth. In fact, researchers now propose that this microbiome impacts directly on the etiology of infertility [49]. In this context, it now seems plausible to propose that β-defensins evolved to regulate the microbiome in seminal fluid and prevent the growth of bacterial populations that may be detrimental to either sperm quality or uterine health.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous work we compared human kinases and kinases of pathogens (Plasmodium, Trypanosoma, Leishmania) and showed that in spite of quite conserved structure of the catalytic domain and binding sites in particular, creation of selective inhibitors is possible [62]. The proposed classification of STPKs is the first step towards developing effective selective inhibitors of bacterial protein kinases.…”
Section: Resultsmentioning
confidence: 99%
“…Further analysis showed that only Anaerococcus was significantly associated with compromised sperm quality. Recently Weng et al have conducted a similar research using 96 samples [62], of which 60 had one or more defects in semen parameters. The rest 36 samples were normal and used as control.…”
Section: The Microbiome Of the Reproductive System Of Menmentioning
confidence: 99%